DETERMINAN KEBERMANFAATAN SISTEM APLIKASI KEUANGAN TINGKAT INSTANSI MENGGUNAKAN MODEL TERINTEGRASI UTAUT, DELONE & MCLEAN, SERTA HOT-FIT DENGAN KOMPETENSI SEBAGAI PEMODERASI : DETERMINANTS OF THE USEFULNESS OF INSTITUTIONAL-LEVEL FINANCIAL APPLICATION SYSTEMS USING AN INTEGRATED UTAUT, DELONE & MCLEAN, AND HOT-FIT MODEL WITH COMPETENCE AS A MODERATING VARIABLE - Dewi, Komang Trisyani Melinia; Musmini, Lucy Sri; Diatmika, I Putu Gede (e-Journal Ekonomi Bisnis dan Akuntansi, 2026)
Evaluating the usefulness of government financial information systems has become increasingly important following the mandatory implementation of the Institutional-Level Financial Application System (SAKTI). This study aims to analyze the determinants of usage intention and net benefit of SAKTI by integrating the UTAUT, DeLone and McLean, and the HOT-Fit framework, with user competence as a moderating variable. This research employs a iquantitative approach using a isurvey method involving employees of the Directorate General of Treasury and State Treasury Service Offices in Bali Province. Data were analyzed using PLS-SEM. The results indicate that usage intention has a positive and significant effect on net benefit, while user competence negatively and significantly moderates this relationship. These findings suggest that at higher levels of competence, system benefits are more strongly influenced by users’ capabilities than by theiri intentioni to use the system. This study concludes that the usefulness of SAKTI is determined by the integrated interaction of human, organizational, and technological factors